PERBADINGAN TEBAL PERKERASAN JALAN LENTUR MENGGUNAKAN METODE ANALISA KOMPONEN DAN BINA MARGA 2017 - Wuon, Orva E.; Lamusu, Rahman; Lawodi, Yulisnawati; Bansambua, Elce M.; Abulebu, Henny I. (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
The issuance of Circular Letter from the Director General of Highways No. 04/SE/Db/2017 With the revision of the 2017 Pavement Design Guidelines, the old flexible pavement design rules no longer apply. However, in some regions, the old Component Analysis guidelines for pavement thickness planning are still being used. This study aims to compare the flexible pavement thickness between the Component Analysis method and Bina Marga 2017. The data used in both methods are the same. The analysis results show differences in pavement thickness between the two methods. The pavement thickness according to the Component Analysis method is as follows: surface layer thickness (D1) = 74 mm, upper foundation layer thickness (D2) = 200 mm, and lower foundation layer thickness (D3) = 250 mm. Meanwhile, the MDPJ 2017 method gives the following thicknesses: surface layer thickness (D1) = 100 mm, upper foundation layer thickness (D2) = 400 mm, and lower foundation layer thickness (D3) = 100 mm. A significant difference between Component Analysis and MDPJ 2017 is that the Bina Marga 2017 method does not take regional factors into account. It assumes that the road drainage system functions properly and there is no water pooling on the road. The smallest load on the road is a 2-ton vehicle, so motorcycles are not considered a load on the road. If the MDPJ 2017 method is used for road planning in areas where the majority of vehicles are motorcycles, it will result in higher implementation costs compared to Component Analysis. In general, the pavement structure according to Bina Marga 2017 is thicker compared to the Component Analysis method, and the CBR value and the number of vehicles are the main parameters in road pavement thickness analysis for both methods mentioned.